The Influence of Billiard Rental Marketing Mix on Visiting Decisions - Trianto, Yosua Andi; Indrawati, Nur (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose –  This study aims to examine the effect of the marketing mix (product, price, place, and promotion) on consumer visiting decisions at Amorty Billiards Training Ground, Dinoyo, Malang.    Design/methodology/approach –  This study employs a quantitative research approach. The population consists of consumers of Amorty Billiards Training Ground in Dinoyo, Malang; however, due to its unknown and dynamic nature, the sample size was determined using the Lemeshow formula, resulting in 100 respondents. Data were collected using structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25.   Findings – The results show that product, price, and place have a positive and significant effect on consumer visiting decisions, while promotion does not have a significant effect. These findings indicate that physical and value-based aspects of the marketing mix play a more dominant role in attracting customer visits compared to promotional activities.   Originality/value – This study contributes to the marketing services literature by examining the role of the marketing mix in influencing visiting decisions in the context of a billiards entertainment business. The findings provide practical implications for business managers, particularly in improving promotional strategies especially through social media to increase consumer awareness and visitation rates.